Connecting Cycling to Transit: A Typology of Toronto Region Commuter Rail Passengers. (June 2018) - Schofield, James; Mitra, Raktim
Highest Scoring Abstract: Undergraduate/Masters: Background: Nearly one in four trips to commuter rail stations in the Toronto region are between one and five kilometers in length – a reasonable distance for cycling. Yet only 1% of passengers arrive by bike, with the majority (62%) of nearly 100, 000 daily passengers driving and parking at a station. A sixteen-billion-dollar investment in enhanced rail service is expected to double current train ridership. To support this growth, it is necessary to increase the use of non-parking-dependent station access modes. Cycling has potential to be a sustainable alternative for short station access trips, while also promoting superior health outcomes associated with a more active lifestyle. This study develops a cycling typology of passengers to foster a better understanding of customer perceptions and to identify customer segments who may be willing to cycle to the station. Methods: Passengers intercepted at three suburban commuter rail stations were invited to complete an online survey (n = 300). Drawing on proven cycling determinants from the literature, the survey assessed willingness to cycle in adverse weather, the importance of end-of-trip facilities, comfort cycling on various types of infrastructure, and other personal identity and societal factors. A principal component analysis of the survey data followed by k-means cluster analysis was used to develop a typology of respondents. Results: Using six factors derived from 17 survey variables, four distinct types of cyclists were identified: All-around cyclists (10%) most frequently cycle for transportation purposes and are most comfortable cycling in adverse weather conditions. Recreational cyclists (29%) frequently cycle for recreation but rarely for transportation purposes and are more comfortable on low-stress facilities such as paths, residential streets, and protected bike lanes than on busy roads. The safety-conscious (33%) do not frequently cycle, but express comfort with low-stress facilities. Finally, the facility-demanding (28%) express the strongest support for end-of-trip facilities and are least likely to agree that cycling is a practical way to reach the station. Nearly all (95%) of those who currently cycle to a station fall within the all-around type. Females are nearly twice as likely as males to be represented in the safety-conscious type. Conclusions: Efforts to increase cycling to rail stations will necessitate encouraging recreational cyclists and the safety-conscious to ride for transportation purposes. Low-stress cycling networks surrounding the stations are critical in supporting these efforts, particularly for female riders.